Anticoagulants for atrial fibrillation: from warfarin and DOACs to the promise of factor XI inhibitors - Kumar, Vineet; Ilkhanoff, Leonard (Frontiers in Cardiovascular Medicine, 2024)
Anticoagulation is the mainstay of stroke prevention in appropriate patients with atrial fibrillation. Due to advances in pharmacotherapy the anticoagulants used for this purpose have evolved significantly over the past decades with the aim of optimizing effectiveness while minimizing bleeding risks. Though significant improvements have been made toward this goal, bleeding risk remains the major concern with these therapies. An investigational class of agents which inhibit Factor XI have shown promise in pre-clinical and early clinical trials to significantly minimize bleeding while maintaining efficacy against stroke and systemic embolism. This mini-review will discuss anticoagulants currently used for stroke prevention in patients with atrial fibrillation including warfarin and direct oral anticoagulants. We will also review the mechanism of action and data from early clinical trials for Factor XI inhibitors and discuss their potential advantages and shortcomings.